Just one look : a novel - Cameron, Lindsay (Ballantine Books, 2021)
"As I stepped off the elevator on the second floor, I found myself silently begging for a calamity. A fire, a flash flood, even a tiny earthquake would suffice. Anything that would give me a legitimate reason to evacuate the area immediately. Or, better yet, I wouldn't make it out in time and the somber voice of Brian Williams would detail my demise on the nightly news. "Cassie Woodson entered the Midtown office building on the first day of her new job mere seconds before the entire skyscraper was reduced to rubble by the powerful explosion.""--